Efektivitas Pemanfaatan Media Online dalam Pembelajaran di Masa Pandemi Covid-19 - Hasan Basri; Lely Fathiyatus Sa’diyah; Siti Nur Khasanah; Danial Hilmi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
This research aims to determine what applications are used by lecturers and students in learning and how it's effectiveness in supporting the learning process. The approach used in this research is qualitative, with data collection through observation, documentation, and interviews. To test the validity of the data, triangulation of sources, data and discussions with peers was used. Data was collected by interview via WhatsApp to ten students of UIN Maulana Malik Ibrahim Malang. The result shows that lecturers and students using apps Zoom Meeting, Google Meet, E-learning and WhatsApp Group to support learning online. Lectures with these media often have problems with the signal or internet network, especially for students who live in areas with poor signal and do not use wifi and that will also have an impact on the quality of learning that students receive. However, this application media is still considered effective by the majority of students, because it has advantages in practicality, saves costs and time, and facilitates communication between lecturers and students.